(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2011)
Today at the dawn of modem education era, we are constantly facing new opportunities and challenges. Professional education in particular faces a Herculean challenge of bridging the gap between traditional classroom lessons and changing industry scenario. Consequently educators today are exploring alternative pedagogy methodologies to capture student attention. One such approach, Activity Based Learning, brings together thinking, doing and learning to make education an experience beyond mere memorizing. This paper aims at illustrating successful case studies of ABL systems and design of similar activities for practical implementation in a professional education curriculum.